Understanding and integrating gender issues into livestock projects and programmes : a checklist for practitioners. (FAO, 2013)
"In rural societies, where local culture and traditions are still very vibrant, responsibilities and tasks are often assigned to women and men on the basis of traditional gender roles, defined as those behaviours and responsibilities that a society considers appropriate for men, women, boys and girls. These roles change over time, have different characteristics in every local context and are shaped by ideological, religious, cultural, ethnic and economic factors. They are a key determinant of the distribution of resources and responsibilities between men and women (FAO, 2010b). In many cases gender roles are biased and favour certain social constituencies at the expense of others. Rural women, for instance, face serious obstacles more regularly than men, since traditional structures and perceptions tend to prevent them from obtaining the necessary tools to reach their full potential in the agricultural sector. In fact, despite their major involvement in and contribution to livestock management, women tend to have limited access to resources, extension services and less participation in decision making compared to their male counterparts (FAO, 2011a). Recognizing the different roles that women and men play in the agriculture sector is key to identifying the diverse challenges they face and tailoring projects and programmes on their specific needs. Understanding and integrating these diverse roles and specific dynamics into projects and programmes can significantly improve their outcomes and effectiveness (FAO, IFAD, World Bank, 2007; FAO, 2011a)."--Publisher's description